Ulmus parvifolia Modulates Platelet Functions and Inhibits Thrombus Formation by Regulating Integrin αIIbβ3 and cAMP Signaling - Irfan, Muhammad; Kwon, Hyuk-Woo; Lee, Dong-Ha; Shin, Jung-Hae; Yuk, Heung Joo; Kim, Dong-Seon; Hong, Seung-Bok; Kim, Sung-Dae; Rhee, Man Hee (Frontiers in Pharmacology, 2020)
Background: The prevalence of cardiovascular diseases (CVDs) is increasing at a high rate, and the available treatment options, sometimes, have complications which necessitates the need to develop safer and efficacious approaches. Ethnomedicinal applications reportedly reduce CVD risk. Ulmus parvifolia commonly known as Chinese Elm or Lacebark Elm, is native to China, Japan, and Korea. It exhibits anti-inflammatory, antiviral, and anticancer properties, but its anti-platelet properties have not yet been elucidated. Purpose: To investigate the pharmacological anti-platelet and anti-thrombotic effects of U. parvifolia bark extract. Study design and methods: Human and rat washed platelets were prepared; light transmission aggregometry and scanning electron microscopy was performed to assess platelet aggregation and the change in platelet shape, respectively. Intracellular calcium mobilization, ATP release and thromboxane-B2 production were also measured. Integrin αIIbβ3 activation was analyzed in terms of fibrinogen binding, fibronectin adhesion, and clot retraction. The expression of MAPK, Src, and PI3K/Akt pathway proteins was examined. Cyclic nucleotide signaling pathway was evaluated via cAMP elevation and VASP phosphorylation. Anti-thrombotic activity of the extract was evaluated in vivo using an arteriovenous shunt rat model, whereas its effect on hemostasis in mice was assessed via bleeding time assay. Results: U. parvifolia extract significantly inhibited human and rat platelet aggregation in a dose-dependent manner along with inhibition of calcium mobilization, dense granule secretion and TxB2 production. Integrin αIIbβ3 mediated inside-out and outside-in signaling events, as evidenced by the inhibition of fibrinogen binding, fibronectin adhesion, and clot retraction. The extract significantly reduced phosphorylation of Src, MAPK (ERK, JNK, and p38MAPK), and PI3K/Akt pathway proteins. Cyclic-AMP levels were elevated in U. parvifolia-treated platelets, while PKAαβγ and VASPser157 phosphorylation was enhanced. U. parvifolia reduced thrombus weight in rats and moderately increased bleeding time in mice. Conclusion: U. parvifolia modulates platelet responses and inhibit thrombus formation by regulating integrin αIIbβ3 mediated inside-out and outside-in signaling events and cAMP signaling pathway.